2007
DOI: 10.1111/j.1365-2036.2007.03524.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of allelic heterogeneity for associations between the NOD2/CARD15 gene and ulcerative colitis among North Indians

Abstract: SUMMARY BackgroundThree common disease susceptibility variants in the NOD2 gene are associated with inflammatory bowel disease in Caucasians, but not in Asians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 34 publications
5
33
2
Order By: Relevance
“…The higher prevalence of ileocolonic involvement in Asian patients with CD has been previously commented upon [4]. Isolated ileal disease was seen in only about a quarter of patients, an observation consistent with the rarity of commonly described NOD2 mutations in the Indian population [29,30]. Interestingly, smoking, which is consistently associated with risk of CD in other populations, was not associated with CD in our patients.…”
Section: Discussionsupporting
confidence: 79%
“…The higher prevalence of ileocolonic involvement in Asian patients with CD has been previously commented upon [4]. Isolated ileal disease was seen in only about a quarter of patients, an observation consistent with the rarity of commonly described NOD2 mutations in the Indian population [29,30]. Interestingly, smoking, which is consistently associated with risk of CD in other populations, was not associated with CD in our patients.…”
Section: Discussionsupporting
confidence: 79%
“…This is the first study that demonstrated a link between NOD2 genotype and UC phenotype. Regional heterogeneity within the NOD2 genotype in UC patients shows the importance of the genetic assessment and evaluation of its correlation with the phenotype in different populations [4,5,10,[12][13][14][15]50]. In addition, other potential genetic predictors and detailed information about environmental exposure should be assessed in future studies, because the lowpenetrance genetic effects of common SNPs may largely depend on interaction with other determinant factors.…”
Section: Discussionmentioning
confidence: 99%
“…Three major NOD2 SNPs, two missense [R702W, G908R] and one frameshift (1,007 fs), were shown by independent groups to be associated with susceptibility to CD [6,7,[9][10][11]. By contrast, even though most available data showed no link between NOD2 mutations and susceptibility to UC, a few recent studies have reached different conclusions, and so this matter remains somewhat controversial [4,5,10,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The above NOD2 gene mutations, particularly when two occur simultaneously in an individual, have been associated with severe and complicated CD [24]. Juyal et al studied 298 UC, 25 CD, and 262 controls in northern India and did not find any of these 3 common mutations [25]. Pugazhendhi et al studied 82 patients with CD and 149 controls and did not find evidence of these 3 mutations in any of the participants [26].…”
Section: The Prevalence Of CD In Indian Immigrants To Developed Countmentioning
confidence: 99%